Extraction of antioxidant compounds from olive (Olea europaea) leaf : a thesis present [i.e. presented] in partial fulfilment of the requirements for the degree of Master of Technology in Food Technology at Massey University, Albany, New Zealand - Luo, Helen (Massey University, 2011)
Olive leaves are by products of olive oil industry, which are also regarded as a rich source of antioxidants. The objective of the present work was to extract antioxidant compounds from olive leaves. The effects of extraction conditions on the total phenolic content were investigated. Three extraction methods were used in this research for recovery of phenolic compounds from olive leaves. A multilevel experimental design was implemented with the aim of optimising the recovery of phenolic compounds from olive leaves by using nontoxic water/ethanol-based solvent. The factors considered were (i) the extraction time, (ii) the extraction temperature, (iii) solvent: solid ratio and (iv) the ethanol concentration. The results suggest that a good recovery of phenolic compound from olive leaves may be achieved at 40°C with a solvent/ solid ratio of 30:1 and ethanol concentration of 80 % (v/v). Drying of fresh leaves before extraction is highly recommended to achieve better recovery of important phenolic compounds including oleuropein. Ultrasonic probe may be useful to improve extraction efficiency and also reduce extraction time. The quantitative and qualitative determinations of phenolic compounds were performed by high-performance liquid chromatography (HPLC), which revealed that oleuropein, luteolin-4-O-glucoside, luteolin-7-O-glucoside and apigenin 7-O-glucoside were the major phenolic compounds present. In this study phenolic compounds extracted from olive leaves of two cultivars (Frantoio & Barnea) were analysed. A comparison among two cultivars shows quantitative differences in some phenolic compounds. The antioxidant capacities of the extracts were evaluated by measuring the radical scavenging effect on 1, 1-diphenyl-2-picrylhydrazyl (DPPH) free radical and by using Oxygen Radical Absorbance Capacity (ORAC). Olive leaf extracts exhibited high antioxidant capacity which suggests olive leaf extract is effective in the function of scavenging free radical. The stability of olive leaf extract stored at four temperatures has also been investigated. The results show increasing temperatures caused greater extent of degradation of phenolic compounds. The best storage condition for olive leaf extracts was at -20 °C in absence of light and oxygen.
Keywords: Olive oil by-products; Antioxidants; Phenolic compounds; Olive leaf extraction; Olive leaf extract